Competition and struggle in Ján Kalinčiak’s conception of Romanticism - Marta Fülöpová (Slovenska Literatura, 2022)
The writer, poet, and teacher Ján Kalinčiak (1822 – 1871) is a representative of the strand of Slovak Romantic fiction that accentuates the subject. His oeuvre helps build the individualistic, heroic variant of Slovak Romanticism, putting emphasis on the individual and freedom – also in relation to the nation. For Kalinčiak, Romanticism was not just a way of artistic self-expression, but also a path towards personal heroism. Kalinčiak’s leaning towards Romanticism is demonstrated among other things in the fact that he drew on European schools of thought concerning such issues as the portrayals of knightly characters. These drew on mediaeval models preferred in the poetics of Romanticism. Kalinčiak modelled his literary world on the basis of the concept of noble rivals, equal adversaries and his portrayals abstained from building negative characters. His version of Romanticism is not based on the fight between good and evil, but on the struggle between two competing visions of the world which in their search for authenticity naturally get into conflict. While his historical fiction is undeniably Romantic, his best known work, Reštavrácia ([County elections], 1860) used to be regarded as a transitional piece bearing elements of Realism. Current research, however, regards it as Romantic.